2021
DOI: 10.1063/5.0038306
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic insight towards the impact of polymer architecture and grafting density on structure-dynamics of PEGylated bovine serum albumin and their applications

Abstract: Macromolecules such as proteins conjugated to polyethylene glycol (PEG) have been employed in therapeutic drug applications, and recent research has emphasized the potential of varying polymer architectures and conjugation strategies to achieve improved efficacy. In this study, we performed atomistic molecular dynamics simulations of bovine serum albumin (BSA) conjugated to 5 kDa PEG polymers in an array of schemes, including varied numbers of attached chains, grafting density, and nonlinear architectures. Non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…Copyright 2019 the Royal Society of Chemistry; permission conveyed through Copyright Clearance Center, Inc. Panels C1 and C2 reprinted with permission from ref . Copyright 2021 AIP Publishing.…”
Section: Bioconjugate Simulation Studiesmentioning
confidence: 99%
“…Copyright 2019 the Royal Society of Chemistry; permission conveyed through Copyright Clearance Center, Inc. Panels C1 and C2 reprinted with permission from ref . Copyright 2021 AIP Publishing.…”
Section: Bioconjugate Simulation Studiesmentioning
confidence: 99%
“…Previously, [13] discovered that the secondary structure motif is not specifically responsible for PEG to induce protein stability. Alternatively, the orientation PEG appeared to be the most influential factor inducing stability [14]. Furthermore, the study conducted by Abuchowski et al (1977) proclaimed that amino acid side chains are available for conjugation [15].…”
Section: Effects Of Pegylation On Protein Stabilitymentioning
confidence: 99%
“…It was preferably selected due to its two folding energetic states, which have been significantly characterized and allowed amino acid substitutions at many locations. The WW protein has 34 residues that assist their preparation via solid-phase synthesis of peptides, thus simplifying the linkage of shorter PEG oligomer at a single location [ 14 ]. The PEG consisting four ethylene oxide units was attached at position 19 of a single Asn side chain of the WW domain of the human protein.…”
Section: Effects Of Pegylation On Protein Stabilitymentioning
confidence: 99%
“…How can the attached helical polypeptide prevent the formation of complexes for IFN with other proteins? Such microscopic questions are suitable to be explored via molecular simulation. For example, the attached coiled polymer/polypeptide is revealed to encapsulate the target protein, and sometimes allosterically change the latter’s structure . In previous simulation work, , we showed that, in delivering therapeutic proteins, the hydrophilic zwitterionic peptides with the highest contact preference could be a potential choice.…”
Section: Introductionmentioning
confidence: 99%